Porphyrin-Loaded Lignin Nanoparticles Against Bacteria: A Photodynamic Antimicrobial Chemotherapy Application - Maldonado-Carmona, Nidia; Marchand, Guillaume; Villandier, Nicolas; Ouk, Tan-Sothea; Pereira, Mariette M.; Calvete, Mário J. F.; Calliste, Claude Alain; Żak, Andrzej; Piksa, Marta; Pawlik, Krzysztof J.; Matczyszyn, Katarzyna; Leroy-Lhez, Stéphanie (Frontiers in Microbiology, 2020)
TThe need for alternative strategies to fight bacteria is evident from the emergence of antimicrobial resistance. To that respect, Photodynamic Antimicrobial ChemoTherapy steadily arises in bacterial eradication by using light, a photosensitizer and oxygen, which generates reactive oxygen species that may kill bacteria. Herein, we report the encapsulation of 5,10,15,20-tetrakis(4-hydroxyphenyl)-21H,23H-porphyrin into acetylated lignin water-dispersible nanoparticles (THPP@AcLi), with characterization of those systems by standard spectroscopic and microscopic techniques. We observed that THPP@AcLi retained porphyrin’s photophysical/photochemical properties, including singlet oxygen generation and fluorescence. Besides, the nanoparticles demonstrated enhanced stability on storage and light bleaching. The THPP@AcLi nanoparticles were evaluated as photosensitizers against two Gram-negative bacteria, Escherichia coli and Pseudomonas aeruginosa, and against three Gram-positive bacteria, Staphylococcus aureus, Staphylococcus epidermidis and Enterococcus faecalis. THPP@AcLi were able to diminish Gram-positive bacterial survival to 0.1%, when exposed to low white LED light doses (4.16 J/cm2), requiring concentrations below 5 µM. Nevertheless, the obtained nanoparticles were unable to diminish the survival of Gram-negative bacteria. Through transmission electron microscopy observations, we could demonstrate that nanoparticles did not penetrate inside the bacterial cell, exerting their destructive effect on the bacterial wall; also, a high affinity between acetylated lignin nanoparticles and bacteria was observed, leading to bacterial flocculation. Altogether, these findings allow to establish a photodynamic antimicrobial chemotherapy alternative that can be used effectively against Gram-positive topic infections, using the widely available natural polymeric lignin as drug carrier. Further research, aimed to inhibit the growth and survival of Gram-negative bacteria, is likely to enhance the wideness of acetylated lignin nanoparticles applications.